PENGARUH BULLYING TERHADAP HASIL BELAJAR MELALUI MOTIVASI BELAJAR (STUDI PADA PESERTA DIDIK KELAS V SD DI KECAMATAN KUPANG TIMUR) - Maxsel Koro; Netty E A Nawa; Sumardi W. Ndolu; Odhita Belandina Mada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the direct and indirect relationships between bullying, learning motivation, and learning outcomes among fifth-grade students in seven public elementary schools in East Kupang District. A total of 75 participants were selected using probability sampling based on the Slovin formula. Primary data were collected through validated and reliable questionnaires. The variables examined include bullying as the independent variable, learning outcomes as the dependent variable, and learning motivation as the intervening variable. Data were analyzed using path analysis supported by LISREL 8.8. The analytical results indicate that bullying significantly affects learning outcomes and learning motivation. Learning motivation also shows a significant direct effect on learning outcomes. However, the Sobel test demonstrates that the indirect effect of bullying on learning outcomes through learning motivation is not statistically significant. Thus, learning motivation does not function as a mediating variable in this model. Implications and recommendations for educational practice are discussed.